Islamic Law and Its Implications for Modern World - Mahsun Mahsun (Institut Agama Islam Ngawi, 2011)
Judul Buku : Islamic Law and Its Implications for Modern WorldKarangan : Sayed Hassan AminPenerbit : Scotland U.K., Royston Ltd, 10 Crown Road North, GlasgowTahun Penerbitan : 1989 M.Tebal : 399 halaman, termasuk indeks